MUSIM PEMIJAHAN DAN FEKUNDITAS IKAN SELAIS (Ompok hypophthalmus) DI RAWA BANJIRAN SUNGAI KAMPAR KIRI, RIAU - Charles P.H. Simanjuntak; M. F. Rahardjo; Sutrisno Sukimin (Jurnal Perikanan Universitas Gadjah Mada, 2008)
The aim of this research was to know the reproductive biology of Ompok hypophthalmus included gonadal development stages and spawning season.The study was conducted from June to December 2006 in floodplain of Kampar Kiri River. Samplings were carried out monthly with purposive sampling method. Fish samples were cathed by gillnet, trapnet, hand line and long line. A total of 474 individuals were captured ranged 80-310 mm in total length and 2-143 g in weight. The female and male reached sexual maturity at 115 mm and 214 mm in total length respectively. The spawning season for this species ranges from June to December where a peak season found in October which examined based on variations in gonado somatic index (GSI) and the existence of mature male and females. The fecundity varied from 688-15180 eggs. The correlation coefficient between fecundity with total length and fecundity with weight were very weak. It lead to suggested that the coefficient cannot be used to predict O. hypophthalmus fecundity.